VALIDITAS HADIS TENTANG JUAL BELI GHARAR - Hamnah Hamnah (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2021)
The Qur'an is a source of Islamic law that is Qath'I, where all of its people must obey the laws that exist in it and no one disagrees or refutes it. Hadith is a source of Islamic teachings, which is second to the Qur'an. From the point of view of the narration, it is clear that there is a difference between the Hadith and the Qur'an. For the Qur'an, all its narrations are mutawatir. While the narration of Hadith takes place in part mutawatir and partly takes place on a week. So starting from here arise various opinions in assessing the quality of hadith. Hadith, even though it is the second source of Islamic law, is still disputed by scholars about its validity to be used as a legal basis, especially those related to vague cases both in the fields of aqidah, worship and muamalah. Currently, what is being discussed a lot is about the validity of the hadith in terms of trade law (buying and selling), especially vague buying and selling (gharar) because it will have an impact on aspects of the sale and purchase results are halal or haram to be used (used and eaten). The validity of this hadith in terms of buying and selling gharar needs to be re-analyzed in terms of its narration, which is related to the sanad and matan aspects. Hadith can only be said to be the second source of Islamic law when its quality is valid, both in terms of sanad and matan. A hadith can only be said to be valid if it meets the criteria for the validity of the hadith sanad, namely: the chain is continued, the narrator is 'fair, the narrator is dhabit, avoids syaz and avoids 'illat. In addition to the validity of the sanad, the validity of the matan is also important to prove the quality of a hadith, according to the jurists, the rules of the validity of the matan hadith are: Not maqlub, not mudraj, not experiencing ziyadah al-Tsiqah, not mudhtarib and not mushahhaf and muharraf.